My planet : finding humor int the oddest places - Roach, Mary (The Reader's Digest Association, Inc., 2013)
Roach takes a magnifying glass to everyday life, exposing moments of hilarity in the mundane and revealing amusing musings about marriage, automated customer service, and mazelike bargain stories.